2020
DOI: 10.3389/fphar.2019.01540
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activity of Lipid-Shelled Nitric Oxide-Loaded Microbubbles

Abstract: The global pandemic of antibiotic resistance is an ever-burgeoning public health challenge, motivating the development of adjunct bactericidal therapies. Nitric oxide (NO) is a potent bioactive gas that induces a variety of therapeutic effects, including bactericidal and biofilm dispersion properties. The short half-life, high reactivity, and rapid diffusivity of NO make therapeutic delivery challenging. The goal of this work was to characterize NO-loaded microbubbles (MB) stabilized with a lipid shell and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Recent research has shown that release of NO from lipid-shelled MBs can occur rapidly within approximately 7 minutes of administration ( Lafond et al., 2020 ); it was therefore important that NOMBs were administered in the SAT immediately after production. Another important step taken in this research was to verify the inclusion of NO within the MB, this was achieved using a nitric oxide colorimetric assay (Abcam, plc.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has shown that release of NO from lipid-shelled MBs can occur rapidly within approximately 7 minutes of administration ( Lafond et al., 2020 ); it was therefore important that NOMBs were administered in the SAT immediately after production. Another important step taken in this research was to verify the inclusion of NO within the MB, this was achieved using a nitric oxide colorimetric assay (Abcam, plc.…”
Section: Discussionmentioning
confidence: 99%
“…The total NO concentration within a 1:5 diluted suspension of DBPC lipid-shelled NOMBs applied to biofilms in this research was 16.5 µM (SD ± 1.45 µM), which is well within the reported range of efficacy for NO mediated treatment of bacterial biofilms ( Barraud et al., 2015 ; Howlin et al., 2017 ). Lafond et al. (2020) , demonstrated quantification of NO concentration by amperometric sensor that showed an average concentration in the suspension of 5 mM in the similarly lipid-shelled Octafluoropropane-NO MB formulation utilised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By enclosing this gas in a shell of acoustically active microbubbles, it is possible to control the release of NO both spatially and temporally by using US. [11,84] Recently, Lafond et al [84] demonstrated the bactericidal efficacy of microbubbles against MRSA plankton when stabilized by a lipid membrane, and loaded with NO alone or combined with octafluoropropane.…”
Section: Microbubblesmentioning
confidence: 99%